World Heritage City Surveillance System by a Smart CCTV System - Kirana Nerngchamnong; Somkuan Kaviya; Yusaku Fujii; Preecha P. Yupapin (My University, 2011)
World heritage city surveillance system using smart closed circuit television (CCTV) is a system that detects the movement around the monitoring area and then counts the number of tourists who enter and exit the word heritage city. The system has been developed to assist the surveillance system in the world heritage city (WHC) or restricted area through the CCTV camera in detecting the trespassers, when the WHC is closed. This data can be used not only for the surveillance purpose but also for the commercial strategic planning and the security community as well. For example, the number of participants, audience, or visitors who attend the event can be used to plan the upcoming event. In developing the world heritage city surveillance system using smart CCTV, the developers adapted the knowledge about image processing to detect and count the number of people-in and people-out from video data and to security for the system. The system was tested on three set of video data and the results reveal 80-90% accuracy rate. Most of the errors occur when the background area is dark or when people walk in a group but the ability to control critical analysis of communication data to the agency administrator can control the order to increase security for tourists and maintain the condition of the remains a world heritage site.
Keywords: Smart City; Video Surveillance and Tracking Methods